The impact of Iraq’s accession to the Convention on Freedom of Association and Protection of the Right to Organize in the reform of the legislative regime of trade union freedoms - ضاحي نايف أحمد (Journal of Legal Sciences, 2019)
In this research, we discussed the following: (The impact of Iraq’s accession to the Convention on Freedom of Association and Protection of the Right to Organize in the reform of the legislative regime of trade union freedoms). This agreement contains a number of basic principles and rights of freedoms and trade union rights: Workers and employers enjoy full freedom to form their unions to protect and promote their interests Without distinction or discrimination between workers. She pointed out that the main impact of Iraq’s ratification of this agreement is to review and reform its labor legislation in accordance with the international standards contained in the Convention on Freedom of Association. The first topic included the legal nature of ILO conventions and the rights of workers to form and join trade unions. The second topic included the other fundamental rights of workers according to the Convention on Freedom of Association and Protection of the Right to Organize.